Sleep quality and quantity in Italian University students: an actigraphic study. (1st November 2020) - Cellini, Nicola; Menghini, Luca; Mercurio, Marco; Vanzetti, Valentina; Bergamo, Damiana; Sarlo, Michela
ABSTRACT: According to international recommendations, young adults should sleep at least 7 h per night and experience good sleep quality to avoid physical and mental health problems. University students are particularly exposed to the risk of sleep issues due to their tendency to go to bed late at night and other social and environmental factors. Here, we aimed to objectively characterize the weekly sleep habits using actigraphy (in terms of quantity, quality, and timing) in 82 Italian university students (mean age = 23.89, SD = 2.51 yrs, 44 women). Exploratory analyses were performed using linear mixed-effect regression to account for several factors (e.g., gender, circadian preferences, depressive symptomatology). We showed that participants spent in bed (TIB) about 7 h and 31 min during weekdays and 7 h and 46 min during the weekend, with 76.83% of the sample showing a TIB longer than 7 h. Women students spent more time in bed than men ( 25 min) and went to bed earlier ( 29 min). One-third of the sample showed a sleep efficiency <85%, whereas 70.73% of the sample showed a wake after sleep onset >40 min, with no differences between men and women. Depressive symptoms, alcohol and coffee consumption affected sleep onset latency, whereas circadian preference was strongly associated with bed and waketime. Moreover, most of the students did not take daytime naps to catch-up with sleep loss. Overall, our sample spent adequate time in bed, but they experienced a moderate low sleep quality, mainly due to high wake after sleep onset.